Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1074/jbc.m404085200
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Growth of Stem Cell Factor and Granulocyte Macrophage Colony-stimulating Factor Involves Kinase-dependent and -independent Contributions from c-Kit

Abstract: Stem cell factor (SCF) binds and activates the receptor tyrosine kinase c-Kit, and this interaction is critical for normal hematopoiesis. SCF also synergizes with a variety of growth factors, including those binding members of the cytokine receptor superfamily. The mechanisms mediating this synergy remain to be defined. The present study investigates both structural and biochemical cross-talk between c-Kit and the receptor for granulocyte macrophage colony-stimulating factor (GM-CSF). We have found that c-Kit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…IgG(5ug/ml) Ab-1(5ug/ml) IL-3(2ng/ml) SCF(50ng/ml) The receptor c-kit has been known for some time to interact with certain other tyrosine kinase receptors including EpoR, GM-CSF receptor (GM-CSFR), and IL-7 receptor, and this physical interaction may be associated with cross-phosphorylation of c-kit by erythropoietin (EPO) or other cytokines (24)(25)(26)(27). The physiologic significance of this cross-phosphorylation has been questioned previously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IgG(5ug/ml) Ab-1(5ug/ml) IL-3(2ng/ml) SCF(50ng/ml) The receptor c-kit has been known for some time to interact with certain other tyrosine kinase receptors including EpoR, GM-CSF receptor (GM-CSFR), and IL-7 receptor, and this physical interaction may be associated with cross-phosphorylation of c-kit by erythropoietin (EPO) or other cytokines (24)(25)(26)(27). The physiologic significance of this cross-phosphorylation has been questioned previously.…”
Section: Resultsmentioning
confidence: 99%
“…EML cells were deprived of SCF and horse serum for 4 h, and 293T cells were deprived of serum for 6 h. This deprivation period was followed by the addition of SCF (50 ng/mL) or IL-3 (4 ng/mL) or the combination of SCF and IL-3. The cells were induced for the indicated times and then were collected and washed with PBS buffer and lysed at 1 × 10 7 cells/mL with ice-cold lysis buffer A (lysis buffer for total cell protein analysis) or lysed at 1 × 10 7 cells/mL with ice-cold lysis buffer B (lysis buffer for immunoprecipitation) as described previously (24). For immunoprecipitation, the lysates were cleared by centrifugation before antibody application.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies reported that KITL has synergistic effects with other cytokines. The effect of KITL on hematopoietic cell lineages to promote their proliferation, differentiation, or survival can be augmented synergistically by combination with other cytokines such as colony stimulating factor-1, -2, or -3 (CSF-1, CSF-2, CSF-3), interleukin-3, and erythropoietin (EPO) (13)(14)(15)(16)(17). We added those cytokines to the medium to elucidate their effects on spermatogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, recent studies have suggested that the physical interaction between KIT and other cytokine receptors could contribute to the cooperation by bringing the two receptors in physical proximity, thereby inducing receptor trans-phosphorylation and activation of downstream substrates. Although, this scenario has been studied to some extent utilizing the KIT/EpoR system, in other receptor systems, including the GM-CSF/SCF system, no evidence for trans-phosphorylation of KIT or the GM-CSF receptor has been reported, however studies have shown the formation of a complex between KIT and the GM-CSF receptor does take place in this system [30]. Thus, the precise role of intracellular tyrosines in KIT mediated co-signaling with cytokine receptors is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, combined stimulation of cells with SCF and GM-CSF results in sustained activation of Mek1/2 and Erk1/2 compared to either cytokine alone [30]. Sustained activation of Erk1/2 is PI-3Kinase dependent in both the SCF/GM-CSF system as well as the SCF/Epo system [29,30].…”
Section: Discussionmentioning
confidence: 99%